ANALYZING NON-PERFORMING ASSETS IN EDUCATIONAL LOANS: A CASE STUDY OF INDIA - PRASANTH, S.; NIVETHA, Dr. P. (The journal of contemporary issues in business and government, 2021)
The primary objective of this research study is to investigate non-performing assets in Indian educational loans. Education is a critical foundation of the Indian economy. It represents the primary source of livelihood for the development and the development of an economy. Educational loans are very important in order to achieve technological development and, implicitly, to reduce costs and use sustainable strategies. The data sample was collected from 80 lenders (bank managers) and 80 borrowers of education loans from Pudukkottai district, Tamilnadu state in India. The Multi Stage Disproportionate Sampling method has been applied for the purpose of collecting information from both the borrowers and the lenders. The analysis results refute the hypothesis, as there is no substantial variation in how various types of banks manage non- performing assets in educational credit, since the bulk of NPA instances in educational credit are the consequence of borrowers' intentional default. The majority of defaults were caused by political leaders' announcements of debt forgiveness. The empirical results are relevant and contribute to a better understanding of the impact of non-performing assets in educational loans on sustainable economic growth in India.